Augmented serum levels of the IGF-I/IGF-binding protein-3 ratio in pre-menopausal patients with type I breast cysts - Enriori, Pablo J. (2003)
Objective: Gross cystic disease (GCD) is the most common benign breast pathology. Although breast cysts are not considered pre-malignant lesions, an increased risk of breast cancer has been reported for patients with type I cysts (Na+/K+ < 3). Furthermore, an augmented IGF-I/IGF-binding protein-3 (IGFBP-3) ratio has been described in breast cancer patients. The objective was to evaluate serum IGF-I and binding protein concentrations of type I and type II cyst patients as compared with healthy women. Methods: Twenty-four patients with type I cysts, 17 with type II cysts and 25 healthy women were evaluated. Serum IGF-I, IGFBP-3 and IGFBP-1 concentrations were measured by IRMA. Results: IGF-I concentrations were significantly higher in sera from patients with type I cysts than in patients with type II cysts. A highly significant decrease of IGFBP-3, the major IGFBP, was found in patients with type I cysts with respect to healthy women, whereas no significant difference was evident between the different cyst types. The IGF-I/IGFBP-3 ratio, an estimate of biologically active IGF-I, was very significantly higher in patients with type I cysts than in both type II patients and healthy women. IGFBP-1 levels were significantly lower in patients with type I than in controls and type II cysts. The IGF-I/IGFBP-1 ratio was significantly higher in patients with type I cysts than in type II bearers and healthy women. Estrogen levels correlated with IGF-I in patients and controls. Conclusions: The enhanced levels of IGF-I/IGFBP-3 found in patients with type I cysts could eventually be associated with the increased risk of breast cancer described for this group.